Dysregulation of Ion Homeostasis by Antifungal Agents - Zhang, Yongqiang; Muend, Sabina; Rao, Rajini (Frontiers in Microbiology, 2012)
Ion signaling and transduction networks are central to fungal development and virulence because they regulate gene expression, filamentation, host association and invasion, pathogen stress response and survival. Dysregulation of ion homeostasis rapidly mediates cell death, forming the mechanistic basis by which a growing number of amphipathic but structurally unrelated compounds elicit antifungal activity. Included in this group is carvacrol, a terpenoid phenol that is a prominent component of oregano and other plant essential oils. Carvacrol triggers an early dose dependent Ca2+ burst and long lasting pH changes in the model yeast S. cerevisiae. The distinct phases of ionic transients and a robust transcriptional response that overlaps with Ca2+ stress and nutrient starvation point to specific signaling events elicited by plant terpenoid phenols, rather than a non-specific lesion of the membrane as was previously considered. We discuss the potential use of plant essential oils and other agents that disrupt ion signaling pathways as chemosensitizers to augment conventional antifungal therapy, and to convert fungistatic drugs with strong safety profiles into fungicides.